2009
DOI: 10.3390/ijerph6102676
|View full text |Cite
|
Sign up to set email alerts
|

Health and Retirement in Europe

Abstract: We use discrete-time hazard models with internationally comparable data from the full eight waves of the European Community Household Panel (ECHP) to study the relationship between retirement and health in nine European countries. Our results provide new evidence of the relationship of health shocks to early retirement. The pattern of results across countries reflects international differences in the incentives created by social security systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(67 reference statements)
2
26
0
1
Order By: Relevance
“…Lindeboom and van Doorslaer (2004) found some evidence of reporting bias by age and gender, but not income, using Canadian data and the constructed McMaster Health Utility Index as their more objective measure. Hagan et al (2006) undertake a similar exercise focusing on the effect of self-reported health on mortality using British data.…”
Section: Introductionmentioning
confidence: 99%
“…Lindeboom and van Doorslaer (2004) found some evidence of reporting bias by age and gender, but not income, using Canadian data and the constructed McMaster Health Utility Index as their more objective measure. Hagan et al (2006) undertake a similar exercise focusing on the effect of self-reported health on mortality using British data.…”
Section: Introductionmentioning
confidence: 99%
“…If given the opportunity, affected individuals may opt for early retirement, part-time employment, or a prolonged sick-leave, either because they objectively cannot perform daily routines or they perceive their health status to be too weak to work. These dynamics have been strongly confirmed in the empirical literature on the effects of sudden and graduated declines in health on the probability to be unemployed, to be inactive, or to retire (Rice et al, 2007;Hagan et al, 2006;Disney et al, 2006;García-Gómez and López-Nicolás, 2006;Wing Han Au et al, 2005;Riphahn, 1999;Bound et al, 1999).…”
mentioning
confidence: 78%
“…Hagan et al found that health exerted a significant and strong impact on the probability of retiring, all else being equal. 45 They used data from nine countries (Belgium, Denmark, France, Greece, Ireland, Italy, Portugal, Spain and the UK) covered by the ECHP for 1994 through 2001, with a sample of individuals aged 50 to 64 and either employed or self-employed in 1994. They used alternative definitions of retirement (self-reported or * An important factor in the decision to retire is an individual's financial incentives, determined largely by the characteristics of the country's pension and social protection system.…”
Section: Health Matters For Retirement (At the Individual Level)mentioning
confidence: 99%
“…Pooling data from all countries revealed that a medium health shock would, all else being equal, increase the probability of retiring by 50 percent, while a large one would increase it by 106 percent ( Table 1). 45 Hagan et al also looked at how the impact of health shocks and health stocks varied among countries, variation that may be associated with the incentives for retirement embedded in a country's social security and tax systems. Despite the cross-country variation, the fundamental results from the pooled analysis presented above did hold through.…”
Section: Health Matters For Retirement (At the Individual Level)mentioning
confidence: 99%
See 1 more Smart Citation